Towards a theory of ecologically unequal exchange (EUE) as a multi-tiered hierarchy: Investigating the interdependence of global and domestic environmental inequalities to explain China's rise to power - Luca Tausch; Jeffrey Althouse (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2024)
The theory of ecologically unequal exchange (EUE) suggests that there exists an asymmetric transfer of biophysical resources from the periphery to the core. Despite ample evidence demonstrating this fact, the theory fails to account for the complex role of the semi-periphery, or how global (inter-country) and domestic (intra-country) environmental inequalities between regions are connected. To fill this gap, we rely on an environmentally extended multi-regional input-output (EEMRIO) model to provide empirical evidence for China's involvement in global (G-EUE) and domestic (D-EUE) ecologically unequal exchange from 1987 to 2017. While being a net exporter of energy to all income groups, we show that China is a net exporter of land, labour, and materials to the core, but a net importer of land, labour, and materials from the periphery and the semi-periphery. On the domestic level, we show that the wealthy East Coast zone is the only net importer of embodied energy and TiVA, while all other economic zones are net exporters of embodied energy to the East Coast zone. While China continues to be exploited by the core, it has fuelled its ascent in the world-system by creating its own peripheries from which it extracts natural resources, as well as by creating extractive peripheries within its borders. Our results suggest the need to move beyond a simple core- periphery dichotomy when studying the world ecological system: EUE arises through a multi- tiered hierarchy that depends on uneven biophysical flows between regions both domestically and globally.
Keywords: Q56; Q57; 330; Ecologically unequal exchange; China; Embodied trade flows; Environmentally extended multi-regional input-output analysis; Inter- and Intra-Country Inequality; International Trade; Structural Decomposition Analysis